1943
DOI: 10.6028/jres.031.019
|View full text |Cite
|
Sign up to set email alerts
|

pH values of acid-salt mixtures of some aromatic sulfonic acids at various temperatures and a criterion of completeness of dissociation

Abstract: A method is described to differentiate between completely and incompletely dissociated acids by means of measurements of the emf of galvanic cells without liquid junctions. Hydrogen and silver-silver-chloride electrodes and solutions of the acid, its sodium or potassium salt, and sodium or potassium chloride are used. The activity coefficients of hydrochloric acid in such mixtures are calculated by the equation relating the emf to the activity of hydrochloric acid in known concentrations of the acid and salts.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
7
0

Year Published

1945
1945
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(7 citation statements)
references
References 19 publications
0
7
0
Order By: Relevance
“…Consequently, the stoichiometrical molalities of KEPh and K 2Ph will be altered and a quantity of H 2Ph formed as a result of the above processes. However, if K2/KI is less than about 10-3 , the tendency of reaction 21 to take place from left to right will be small and mH 2 Ph can be neglected in eq 24 [20] for a-phthalic acid, K2/KI is about 3 X 10-3 which exceeds the condition postulated for the neglect of mH2Ph in eq 24 and 25. Therefore corrections for H 2Ph, sometimes called "overlapping" corrections because H 2Ph and HPh-are titrated simultaneously, become necessary even though they are small.…”
Section: Complete Methodsmentioning
confidence: 93%
See 1 more Smart Citation
“…Consequently, the stoichiometrical molalities of KEPh and K 2Ph will be altered and a quantity of H 2Ph formed as a result of the above processes. However, if K2/KI is less than about 10-3 , the tendency of reaction 21 to take place from left to right will be small and mH 2 Ph can be neglected in eq 24 [20] for a-phthalic acid, K2/KI is about 3 X 10-3 which exceeds the condition postulated for the neglect of mH2Ph in eq 24 and 25. Therefore corrections for H 2Ph, sometimes called "overlapping" corrections because H 2Ph and HPh-are titrated simultaneously, become necessary even though they are small.…”
Section: Complete Methodsmentioning
confidence: 93%
“…As a result of these equilibria, in a solution composed of KEPh of molality of ml and of K2Ph of a molality of m2 (24) as HPh-is removed in process 20 to form H+ ions and in process 21 to form H2Ph. Also mPh=m2+mH+mH2Ph, (25) as HPh-is removed in process 20 in an amount equivalent to H+ ions and in process 21 in an amount equivalent to H 2Ph.…”
Section: Complete Methodsmentioning
confidence: 99%
“…If a equals the molality of the acid and b the molality of added alkali, then for any mixture of the two (13) (14) By the use of these equations and eq 3 and 8, eq 15, (15) (16) obtained by the elimination of mH2Ph, mHPh, and mph in eq 3, 8, 10, and 11, is satisfied for the solutions of any composition and concentration. However, solution of eq 15 requires a knowledge of mH, the activity coefficients, K …”
Section: Complete Methodsmentioning
confidence: 99%
“…The "cutoff" positions of many buffer compounds of about O.OI-M concentration have already been determined in l-cm absorption cells. 4 In order to prevent distortion of the spectrophotometric curves by specific salt errors, it is desirable to keep the ionic strength of each buffer as low as possible, without sacrifice of buffering capacity. In earlier published work on the acid range of metacresolsulfonphthalein in the visible region [8], it was shown that the intermediate and complete transformation of this indicator could be accomplished simply by the use of solutions of hydrochloric acid of concentrations ranging from about 10-3 to 2 M. Provisional measurements of several other indicators in the visible and in the ultraviolet have now been obtained by use of phthalates, benzoates, citrates, phosphates, and phellolsulfonates, in addition to hydrochloric acid and sodium or potassium hydroxide.…”
Section: Selection Of Buffersmentioning
confidence: 99%
“…The dissociation of the two groups of p-phenolsulfonic acid has also been recently studied by electromotive-force methods [3,4]. The esters of p-hydroxybenzoic acid are representative of compounds difficulty soluble in water.…”
mentioning
confidence: 99%